A review of Fiqh al-Muamalat subjects in economics and related programs at International Islamic University Malaysia and University of Brunei Darussalam - Mat, Ismail; Ismail, Yusof (2008)
Fiqh al-mu'amalat subjects have become core subjects in the Kulliyyah of Economics and Managements Sciences (KENMS), International Islamic University Malaysia (HUM) as an institution of higher learning since its establishment in 1983. The same discipline of fiqh was also introduced in the Faculty of Business, Economics and Policy Studies, Universiti Brunei Darussalam (UBD). The establishment of IIUM was based on the recommendation of the First World Conference on Muslim Education held in Mecca in 1977. In conjunction with thirty years of research in Islamic economics, it would be of paramount importance to review and evaluate the contribution of fiqh mu'amalat subjects in strengthening the structure and contents of Islamic economicsl . As an academic discipline, Islamic economics has been introduced in a number of institutions of higher learning throughout the Muslim world and in the West. As apparent in previous research in the field of Islamic economics, the rules and guidelines of fiqh mu'amalat have been incorporated in the formulation of Islamic economics both in teaching and research. Hence, this paper attempts to critically review and assess fiqh mu'amalat subjects in economics and related programs at IIUM and UBD in order to uncover their contribution and significance in developing Islamic economics discipline.